Allergen immunotherapy for allergic asthma: protocol for a systematic review. Issue 1 (December 2015) - Dhami, Sangeeta; Nurmatov, Ulugbek; Agache, Ioana; Lau, Susanne; Muraro, Antonella; Jutel, Marek; Roberts, Graham; Akdis, Cezmi; Bonini, Matteo; Calderon, Moises; Casale, Thomas; Cavkaytar, Ozlem; et al.
Abstract Background The European Academy of Allergy and Clinical Immunology (EAACI) is in the process of developing the EAACI Guidelines for Allergen Immunotherapy (AIT) for Allergic Asthma. We seek to critically assess the effectiveness, cost-effectiveness and safety of AIT in the management of allergic asthma. Methods We will undertake a systematic review, which will involve searching international biomedical databases for published, in progress and unpublished evidence. Studies will be independently screened against pre-defined eligibility criteria and critically appraised using established instruments. Data will be descriptively and, if possible and appropriate, quantitatively synthesised. Discussion The findings from this review will be used to inform the development of recommendations for EAACI's Guidelines on AIT.